(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Tuberculosis (TB) is one of the oldest and most dangerous infectious diseases in human history, claiming millions of lives annually. In recent decades, multidrug-resistant tuberculosis (MDR-TB) in particular has become a serious threat to global public health. MDR-TB is characterized by the resistance of mycobacteria to at least two essential first-line drugs: isoniazid and rifampicin. Treating this condition is significantly more complex, lengthy, and costly, and is associated with high rates of treatment failure and mortality